3D reconstruction of ATFL ligament using ultrasound images - Singh, V. (IEEE Computer Society, 2014)
Among all existing medical imaging modalities such as MRI, CT, PET and SPECT, ultrasound (US) imaging is one of the most widely used in various applications such as ligament injuries, tendon injuries, bone injuries, cardiac imaging, blood flow estimation and obstetrics. Although Three-Dimensional Ultrasound (3D-US) has many benefits such as non-invasive, low cost, portable, real-time and non-ionizing, however, it is limited in diagnosis and management of obstetrics and atherosclerosis, thus far. Since the current Two-Dimensional Ultrasound (2D-US) has many limitations in the diagnosis of ligament injuries and abnormalities. This study represents the 3D Ultrasound Reconstruction of Anterior talofibular Ligament (ATL) for obtaining the fruitful information for disease diagnosis and progression. Â© 2014 IEEE.